Trajectories of psychological distress after prison release: Implications for mental health service need in ex-prisoners - Thomas, E.; Spittal, M.; Heffernan, E.; Taxman, F.; Alati, Rosa; Kinner, S. (Cambridge University Press, 2016)
© Cambridge University Press 2015. Background Understanding individual-level changes in mental health status after prison release is crucial to providing targeted and effective mental health care to ex-prisoners. We aimed to describe trajectories of psychological distress following prison discharge and compare these trajectories with mental health service use in the community. Method The Kessler Psychological Distress Scale (K10) was administered to 1216 sentenced adult prisoners in Queensland, Australia, before prison release and approximately 1, 3 and 6 months after release. We used group-based trajectory modeling to identify K10 trajectories after release. Contact with community mental health services in the year following release was assessed via data linkage. Results We identified five trajectory groups, representing consistently low (51.1% of the cohort), consistently moderate (29.8%), high increasing (11.6%), high declining (5.5%) and consistently very high (1.9%) psychological distress. Mood disorder, anxiety disorder, history of self-harm and risky drug use were risk factors for the high increasing, very high and high declining trajectory groups. Women were over-represented in the high increasing and high declining groups, but men were at higher risk of very high psychological distress. Within the high increasing and very high groups, 25% of participants accessed community mental health services in the first year post-release, for a median of 4.4 contact hours. Conclusions For the majority of prisoners with high to very high psychological distress, distress persists after release. However, contact with mental health services in the community appears low. Further research is required to understand barriers to mental health service access among ex-prisoners.